PENGEMBANGAN LKPD BERBASIS KESENIAN JATHILAN MATERI PERKALIAN BILANGAN SD - Eko; Pardimin; Ana Fitrotun Nisa (Tuladha : Jurnal Pendidikan Dasar, 2022)
This research used aims to description of development process of LKPD Mathematics and to know the quality of LKPD resulting from them of multiplication numbers based on Jathilan art. This research use research and development method (R &D) is using to result a certain product it is developing LKPD. Development model used on this research used development model ADDIE consisting of 5 stages, they are analysis, design, development, implementation, and evaluation. The research subject this research are two validators, they are material expert rest validator, design and media expert test validator, and also the target users of this product the students of grade 2 Elementary School. The kind of this data ini this research used form of quality and quantitative data. The instrument is used in this research are questionnaire and study result test. The research result shows: (i) this results producers LKPD based on Jathilan art on valid and practical multiplication material, (ii) the LKPD developed gas a potential effect on student learning outcomes on understanding the concept of multiplication.